방사선사법 제정의 필요성 - 임우택(Woo-Taek Lim); 임청환(Cheong-Hwan Lim)；주영철(Young-Cheol Joo)；홍동희(Dong-Hee Hong)；정홍량(Hong-Ryang Jung)；정영진(Young-Jin Jung); 최지원(Ji-Won Choi); 윤용수(Yong-Su Yoon); 김은혜(Eun-Hye Kim); 유세종(Se-Jong Yoo); 박명환(Myeong-Hwan Park); 양오남(Oh-Nam Yang); 정봉재(Bong-Jae Jeong) (방사선기술과학, 2021)
According to the changes of the medical environment of the times, it is necessary to discuss the issues of the doctor's medical guidance and to conduct continuous research so that alternatives can be prepared systematically. Furthermore, in order to enhance the professionalism of radiological technologists and to develop the medical technician system, the new Radiological Technologist Independent Act has been established, which contains the overall contents of the scope of work, professional qualifications, and specialized education of radiological technologists, and provides quality medical services to patients through professional procedures and treatment. In order to increase the level of medical care, the purpose, definition, mission, role, and scope of work specified in the Medical Act, Medical Service Technologists, etc. Act, the Enforcement Decree, and the Enforcement Rules were variously analyzed and new directions were presented. First, the definition of a medical technician should use a generic term so that the factors of conflict and prejudice could be resolved. Second, change the doctor's guide to doctor's prescription; and then legislate the authority to sign and write medical records after examination by radiological technologists, thereby prohibiting unlicensed technicians that seriously endanger patient safety. Third, an accurate definition of radiological technologists' roles should be established; not only selection and management of radiological technologists' work but also procedures and treatment for each radiology field should be specified to suit the current medical system. Fourth, a professional radiological technologists' qualification system and a specialized education system should be established in order to secure human resources that could provide patients trust in procedures and treatment based on professional knowledge and experience in the field of radiology. Fifth, the Education and Evaluation Institute should be operated in Korea education system to educate the professional knowledge and competency for students. In addition, it is necessary to in-depth analysis of foreign cases could be applied to the medical system and education system in Korea; it could strive to nurture systematic human resources.